Empirical study on asymmetric cost behavior: analysis of the sticky costs of local public enterprises / Shoichiro Hosomi and Shohei Nagasawa - Hosomi, Shoichiro; Nagasawa, Shohei (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
This research focused on public sector organizations, especially local public enterprises, and verified their sticky costs using panel data analysis. The results show, contrary to the research hypotheses, that anti-sticky costs arepresent in local public enterprises. We thought that the impact of the water supply business that accounts for about 60% of the sample was high. Then, we further analyzed the sample data by excluding them, and the result nevertheless indicated the presence of sticky costs. Based on these results, it became clear that in local public enterprises, the degree of sticky costs varies depending on the type of industry. It is suggested that the differences for sticky costs may be affected from not only the differences in the business environment but also in the differences in the cost structure for each type of industry, and the differences in legal regulations, market share rates and pricing methods.